2015
DOI: 10.1007/s11064-015-1609-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Intrauterine Growth Restriction on the Regional Neurochemical Profile of the Developing Rat Brain

Abstract: Background Intrauterine growth restricted (IUGR) infants are at increased risk for neurodevelopmental deficits that suggest the hippocampus and cerebral cortex may be particularly vulnerable. Objective Evaluate regional neurochemical profiles in IUGR and normally grown (NG) 7-day old rat pups using in vivo 1H magnetic resonance (MR) spectroscopy at 9.4T. Methods IUGR was induced via bilateral uterine artery ligation at gestational day 19 in pregnant Sprague Dawley dams. MR spectra were obtained from the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…As such, numerous oxidative reactions would have begun and eventually led to oxidative injury. In the present study, the IUGR-induced increased hepatocyte apoptosis as well as necrosis level detected by Annexin V-FITC staining agreed with prior research in brain, 42 kidney, 43 small intestine 8 and placenta. 44 Such nding suggested that IUGR inuenced liver development as well as metabolism through increasing apoptotic activity.…”
Section: Discussionsupporting
confidence: 93%
“…As such, numerous oxidative reactions would have begun and eventually led to oxidative injury. In the present study, the IUGR-induced increased hepatocyte apoptosis as well as necrosis level detected by Annexin V-FITC staining agreed with prior research in brain, 42 kidney, 43 small intestine 8 and placenta. 44 Such nding suggested that IUGR inuenced liver development as well as metabolism through increasing apoptotic activity.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, multislice MRI data did not have sufficient 3D spatial resolution for an accurate assessment of CSF in selected VOIs. We decided to use MM content as a reference for these two reasons: (a) reliability and precision of MM quantification was very high (CRLB = 1–2% in cerebellum); (b) we have not observed significant differences in MM content between experimental and control groups in any of the developing rat or mouse models we have investigated over the last two decades 13,16,24,41–44 . In addition, MM content was nearly identical in the hippocampus of jaundiced and control rats of the present study (difference = 0.6%, p = 0.85).…”
Section: Discussionmentioning
confidence: 70%
“…30 Animal models of FGR have shown oxidative stress and mitochondrial dysfunction in the brain 31 with decreased concentrations of GSH in various cerebral cortex regions, including the temporoparietal, frontal, and occipital lobes after 90 minutes of hypoxia. 32 This suggested that the cortex may be more vulnerable to injury due to oxidative stress than other regions and this may have long-term neurodevelopmental implications.…”
Section: Discussionmentioning
confidence: 99%